Updated evidence on malaria risk associated with irrigated rice in sub-Saharan Africa - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The synoptic review and meta-data analysis is currently online with ‘Preprints with The Lancet (part of the Social Science Research Network's First Look).